Analisis Pengaruh Kualitas Produk, Kualitas Pelayanan, dan Citra Merek terhadap Minat Beli Ulang pada Sepatu Nike Running di Semarang melalui Kepuasan Pelanggan sebagai Variabel Intervening - Ramadhan, Afif Ghaffar; Santosa, Suryono Budi (Diponegoro Journal of Management, 2017)
The aim of this study is to analyse the effects of the product quality, the service quality, and the brand image towards consumers’ repurchase intention of Nike running shoes by using customer’s satisfaction as this study’s mediator variable (intervening) of Nike running consumers in Semarang. The quality of Nike running shoes is what attracts the consumers to repurchase another Nike shoes as well as what satisfies them. The strategy used by Nike to maintain its brand image is to do innovations by developing design and material to create an excellent running shoes product. A company which is able to maintain its service quality is of course able to maintain its consumers by constantly making them satisfied by its products. The sample of this study is taken using non probability sampling, which are the people who have previously bought Nike running shoes in Semarang. Data are collected of 150 Nike running shoes consumers with questionnaire technique. This study uses maximum likelihood as an analysis method by using Amos program version 22.0. The analysis results show that the product quality, the service quality, and the brand image have positive and significant impacts on consumers’ satisfaction. The product quality and the service quality have negative and insignificant impacts on consumers’ repurchase intention. The brand image has positive and significant impacts on consumers’ repurchase intention. While the brand image has negative and insignificant impacts on consumers’ repurchase intention.